The Role of Inflation, Bank Indonesia Sharia Certificates, and the Jakarta Islamic Index on State Sharia Securities - Selliamanik, Irma Selliamanik; Adytio, Erlangga; Markonah, Markonah (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose –This study aims to analyze the effect of inflation, Bank Indonesia Sharia Certificates (BISC), and the Jakarta Islamic Index (JII) on State Sharia Securities (SSS). Methodology/approach – The population used in this study is inflation, Bank Indonesia Sharia Certificates, Jakarta Islamic Index and State Sharia Securities in the 2016-2020 period as many as 60 data with a sampling technique, namely clear sampling of 60 data. This study was analyzed using the Multiple Linear Analysis method.Findings – The results of Multiple Linear Regression Analysis are as follows: Y = 1388.145 – 5.171 X1 + 0.032 X2 – 1.665X3 The study was conducted using time series data for the period 2016 to 2020. The results showed that inflation had a significant negative effect on SSS , BISC has a significant positive effect on SSS, and JII has a significant negative effect on SSS. From the results of the R-square Coefficient of Determination test that Inflation, BISC, and JII have an influence of 55.6% on SSS.Novelty/value – The higher the Bank Indonesia Sharia Certificates (BISC), the higher the State Sharia Securities (SSS). Keywords: Inflation, BISC, Jakarta Islamic Index, SSS